Analysis of the No-Claim Discount system and the proposed modification: a case study in Malaysia - Haslifah Hashim,; Nurin Haniah Asmuni, (Penerbit ukm, 2009)

(untitled)
The No-Claim Discount (NCD) is a system that adjusts the premium paid by policyholders according to their individual insurance claim history. The current NCD system in Malaysia is not protecting good drivers more than bad drivers. Good drivers, who are in the maximum discount group are being penalised unfairly more than those in the 0-percent discount level. Therefore, this paper introduces an alternative step-back NCD system with additional classes and a malus zone, which is rather “tough” to policyholders. The idea is that the bonuses awarded to good drivers should be compensated for by maluses from bad drivers. The main actuarial tools for evaluating and comparing different NCD systems are then used in this study in terms of the fairness of penalty charges to policyholders, the total difference of premium income collected by insurance companies and the efficiency of the systems